1998
DOI: 10.1046/j.1469-1809.1998.6240291.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Australian Crohn's disease pedigrees refines the localization for susceptibility to inflammatory bowel disease on chromosome 16

Abstract: A number of localizations for the putative susceptibility gene(s) have been identified for both Crohn's disease and ulcerative colitis. In a genome wide scan, Hugot et al. (1996) identified a region on chromosome 16 which appeared to be responsible for the inheritance of inflammatory bowel disease in a small proportion of families. Subsequent work has suggested that this localization is important for susceptibility to Crohn's disease rather than ulcerative colitis (Ohmen et al. 1996; Parkes et al. 1996). We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(30 citation statements)
references
References 25 publications
0
28
1
1
Order By: Relevance
“…The genetic component appears to play a more important role in the pathogenesis of CD than in UC [Tysk et al, 1988;Thompson et al, 1996]. Genome wide screening identified the IBD1 susceptibility locus on the pericentromeric region of chromosome 16 [Hugot et al, 1996], which has been replicated in several independent populations [Ohmen et al, 1996;Cavanaugh et al, 1998;Cho et al, 1998;Curran et al, 1998;Annese et al, 1999]. Recently, two independent groups identified Caspase Activating Recruitment Domain (CARD15), previously reported as NOD2, as the gene conferring susceptibility of CD in the IBD1 locus [Hugot et al, 2001;Ogura et al, 2001a].…”
Section: Introductionmentioning
confidence: 95%
“…The genetic component appears to play a more important role in the pathogenesis of CD than in UC [Tysk et al, 1988;Thompson et al, 1996]. Genome wide screening identified the IBD1 susceptibility locus on the pericentromeric region of chromosome 16 [Hugot et al, 1996], which has been replicated in several independent populations [Ohmen et al, 1996;Cavanaugh et al, 1998;Cho et al, 1998;Curran et al, 1998;Annese et al, 1999]. Recently, two independent groups identified Caspase Activating Recruitment Domain (CARD15), previously reported as NOD2, as the gene conferring susceptibility of CD in the IBD1 locus [Hugot et al, 2001;Ogura et al, 2001a].…”
Section: Introductionmentioning
confidence: 95%
“…Thus far, the chromosome 16 and 12 loci have demonstrated significant and confirmed evidence for linkage, with multiple other loci demonstrating suggestive evidence. The chromosome 16 locus has been confirmed extensively for CD [22][23][24][25]; only one study has demonstrated linkage in pure UC families [26]. No studies have demonstrated linkage in mixed CD-UC pairs.…”
Section: A Complex Genetic Disordermentioning
confidence: 93%
“…Ein wesentlicher Hinweis auf die Existenz des ersten Krankheitsgens waren Kopplungsstudien [50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,68]. An betroffenen Geschwisterpaare hatte sich so bereits 1996 ein Hinweis auf eine genetische Risikoregion auf Chromosom 16 ergeben.…”
Section: Weiteres Genetisches Risikounclassified